PENGARUH TEMPERATUR DAN WAKTU PROSES TERHADAP KUALITAS MINYAK PIROLISIS LIMBAH PLASTIK LOWDENSITY POLYETHYLENE - Dara Rizky Rivaldo Rijadi; Erry Ika Rhofita; Shinfi Wazna Auvaria (Scientific Journal of Mechanical Engineering Kinematika, 2025)
The underutilization of plastic waste leads to environmental and health degradation. Utilizing plastic waste as an alternative fuel through pyrolysis is a precise choice for reducing waste quantity and improving environmental quality. This study aims to determine the effect of temperature and pyrolysis time of low-density polyethene (LDPE) plastic waste on the quality of pyrolysis oil. A laboratory-scale fixed batch reactor set to three temperature variations of 520, 550, and 580°C with processing times of 90 and 120 min was used to produce pyrolysis oil from plastic waste. The results showed that to produce more than 55% of pyrolysis yield, it is necessary to increase the processing time by 30 minutes at a temperature of 520°C. Increasing the process temperature to 580°C increased the density and viscosity of pyrolysis oil to 823 kg/m³ and 20 cSt, respectively. However, the calorific value will decrease by 4 MJ/kg; it is mixed with other biofuel products to reduce its viscosity value.